RESULTS OF STUDY OF THE FORM OF THE GEOIDAL SURFACE IN ANTARCTICA (Rezultaty Issledovanii Formy Poverkhnosti Geoida v Antarktide) - Frolov,A. I. (1969)
Because of hydrological and geophysical investigations in Antarctica carried out by various countries, it is possible to present in the first approximation the structure of the sub-glacial relief and gravity field of considerable sections of the Antarctic continent and ocean. (Author) Trans. of Morskie Gravimetricheskie Issledovaniya (USSR) v3 (covers 1960-65) p99-112 1967, by Walter L. Burton.